Enhancing BIM implementation in the Ethiopian public construction sector: An empirical study. Issue 1 (1st January 2021) - Belay, Solomon; Goedert, James; Woldesenbet, Asregedew; Rokooei, Saeed
Abstract: Recently, the popularity of BIM has grown rapidly in the public construction sector. However, only a few studies so far have been seeking to address the BIM adoption benefits and barriers in developmental public projects across the low-income countries. Thus, the study aims to investigate the benefits and barriers of BIM adoption in the context of the Ethiopian infrastructure market. To achieve the objectives, a comprehensive systematic literature review was conducted to identify BIM adoption benefits and barriers in developing countries. Then, a structured questionnaire survey was conducted to collect data from various professionals working in organizations including client, consultant, and contractor. The results indicate that Insufficient IT Infrastructure, Poor Government Help, and Lack of BIM Researches & Courses in Universities are the top ranked BIM adoption barriers in infrastructure projects. Whereas, Improved Communication Among Parties, Early Multidisciplinary Coordination, and 3D visualization perceived as the major benefits of BIM adoption in the Ethiopian context. The findings provide empirical evidences to professionals, business CEOs and policy makers for the development of future BIM adoption policy in the Ethiopian construction sector. Further, insightful recommendations were forwarded to enhance the current BIM uptake in various construction projects.